Penggunaan Spermin dalam Regenerasi Tanaman pada Kultur Antera Beberapa Aksesi Padi Gogo - Bambang S. Purwoko (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2004)
The objective of the research was to determine anther culture ability of 7 rice accessions in an improved media supplemented with spermine. The seven accessions were Hawara Bunar, Grogol, Sigundil. Krowal. CT-650-24-J-3. Lembayau, dan Mendali. Media N6 was used for callus induction and MS was used for regeneration. Both media was supplemented with spermine at J0 -4M . Result of the experiment showed that Grogol. Sigundil. and Lembayau gave green plantlet. Sigundil and Mendali possessed highest anther culture ability and therefore best suited for parent in rice breeding involving anther culture technique. Key words: Anther culture, Spermine, Upland rice, Green plant